Spatial Interpretation: Spatial Configuration of Old Ladoga - G. I. Ostapenko (Сравнительная политика)
This paper considers the way of investigation of stolicnost’ (capitalness) phenomenon on the ground of analysis of entity’s spatial position by forming schemes of spatial patterns (configurations) (by the S.V. Rogachyov’s method). This approach complements necessary, but insufficient way of stolicnost’ (capitalness) studying through identity concept. It implies using interpretation of space stage (in research design) which promotes more detail consideration of phenomenon. Also there were analyzed spatial patterns (configurations) of Staraya Ladoga, which were given appropriate assessment.